Regulation of Heat Shock Protein Responses (Heat Shock Proteins,, 2018)
The book Regulation of Heat Shock Protein Responses provides the most comprehensive review on contemporary knowledge on the regulation of HSP responses and its consequences to human diseases and disorders. Using an integrative approach to understanding the regulation of HSP responses, the contributors provide a synopsis of novel mechanisms by which HSP responses are regulated under normal physiological and pathophysiological conditions. Key basic and clinical research laboratories from major universities and academic medical hospitals around the world contribute chapters that review present research activity and importantly project the field into the future. The book is a must read for researchers, postdoctoral fellows and graduate students in the fields of Translational Medicine, Human Physiology, Biotechnology, Molecular Medicine, Infectious Diseases and Pathology.